2020
DOI: 10.1177/0972753121990143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nature Experience on Fronto-Parietal Correlates of Neurocognitive Processes Involved in Directed Attention: An ERP Study

Abstract: Background: Several studies have demonstrated that brief interactions with natural environments can improve cognitive functioning. However, the neurocognitive processes that are affected by natural surroundings are not yet fully understood. It is argued that the “elements” in natural environment evoke “effortless” involuntary attention and may affect the neural mechanisms underlying inhibition control central to directed attention. Methods: The present study used electroencephalography (EEG) to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
(90 reference statements)
3
5
1
Order By: Relevance
“…Several investigations have found that both alpha and theta power are associated to the activities of mindfulness and meditation ( Aftanas and Golocheikine, 2001 ; Lagopoulos et al, 2009 ; Lomas et al, 2015 ), and therefore these brain waves may be both modulated in the same way during nature experiences in response to a relaxation and positive emotions. This effect seems to be in line with two recent studies [the lab-study of Sahni and Kumar (2020) , and the real-life static exposure study of Chen et al (2020) ] showing that nature videos may modulate both alpha and theta power.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Several investigations have found that both alpha and theta power are associated to the activities of mindfulness and meditation ( Aftanas and Golocheikine, 2001 ; Lagopoulos et al, 2009 ; Lomas et al, 2015 ), and therefore these brain waves may be both modulated in the same way during nature experiences in response to a relaxation and positive emotions. This effect seems to be in line with two recent studies [the lab-study of Sahni and Kumar (2020) , and the real-life static exposure study of Chen et al (2020) ] showing that nature videos may modulate both alpha and theta power.…”
Section: Discussionsupporting
confidence: 90%
“…The results presented in our study, together with the ones presented in previous investigations ( Ulrich, 1981 ; Grassini et al, 2019 ; Sahni and Kumar, 2020 ), showed that experiencing natural environments in various real or computerize forms produces measurable and reliable brain activity markers which are known to be related to cognitive and emotional restorative processes ( Aftanas and Golocheikine, 2001 ; Lagopoulos et al, 2009 ; Baijal and Srinivasan, 2010 ). Therefore, they can be argued to promote restorative processes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of relevance, no significant associations were detected in other frequency bands (e.g., alpha and theta) previously associated with nature exposure and stress reduction (Ulrich, 1981;Chang et al, 2008;Grassini et al, 2019Grassini et al, , 2022Sahni and Kumar, 2020;Koivisto et al, 2022). The discrepancies between previous reports and the current research may be explained by several differences in study designs and methods.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies have shown that mindfulness (Lomas et al, 2015) and meditation (Aftanas & Golocheikine, 2001; Lagopoulos et al, 2009) increase alpha and theta powers, suggesting they are related to relaxed and emotionally positive states. Specifically related to nature exposure, Sahni and Kumar (2020) reported that viewing nature videos increased both alpha and theta powers, suggesting a relaxed yet alert state of mind. Thus, in showing enhancement of theta and alpha activity in nature-related source attribution conditions, especially in persons highly connected to nature, our study suggests that mere attribution of the sound to nature and listening to the sound seems to produce a state of relaxed alertness.…”
Section: Discussionmentioning
confidence: 99%